Analisis Etos Kerja Asn Berakhlak Terhadap Kinerja Pegawai - Azizah, Luluk; Arisyahidin, Arisyahidin (Universitas Islam Kadiri, 2025)
Civil Servants (ASN) play a strategic role as implementers of public policy, contributing significantly to the success of bureaucracy, public service delivery, and national development. Law Number 5 of 2014 underscores the duties of ASN in public service, governance, and development, thereby requiring them to possess high levels of competence, integrity, and work ethic to realize good governance. To support this, the government has established the Core Values of ASN, known as BerAKHLAK, which consist of: Service-Oriented, Accountable, Competent, Harmonious, Loyal, Adaptive, and Collaborative. These core values serve as the foundation for cultivating a positive work ethic, which in turn drives productivity and employee responsibility, ultimately influencing performance. A quantitative study was conducted involving 37 ASN employees in the General Affairs Division of the Regional Secretariat of Blitar Regency. The objective was to analyze the relationship between work ethic, grounded in BerAKHLAK values, and employee performance in the division. The results of hypothesis testing using linear regression analysis revealed a significant influence of work ethic on employee performance, with a significance value of 0.000 and a t-value of 7.681. These findings highlight the importance of strengthening a work ethic based on BerAKHLAK values to enhance ASN performance, which is essential for organizational advancement and improved public service delivery.